Bacterial meningitis in Egypt: analysis of CSF isolates from hospital patients in Cairo, 1977-78 - Guirguis, N. (1983)
Bacterial meningitis remains a major cause of mortality and morbidity in many countries of the world despite effective antimicrobial therapy. Studies of the etiology and some laboratory characteristics of bacterial meningitis in Egypt were conducted during 1977-1978. All patients suspected of having bacterial meningitis were studied at the time of admission to the two fever hospitals of Cairo. Direct culture, serological identification of the capsular type, and countercurrent-immunoelectrophoresis of 1627 CSF specimens were done. Of these, 276 had bacteria identified either by culture or Gram stain. Pneumococci were the most common and the serotype distribution was similar to that reported from other parts of Africa; second were meningococci with groups C and B predominating; in third place was Haemophilus influenzae type b which caused the highest mortality and had an unusually young age distribution. There were 77 bacterial isolates (22%), including 11 species, designated as “other” because there was no predominant species. There were many “clear” CSF specimens that were found to contain pneumococci, meningococci or H. influenzae type b, confirming the need for more comprehensive laboratory facilities for accurate diagnosis of the etiology of bacterial meningitis.